2012
DOI: 10.1038/npp.2012.50
|View full text |Cite
|
Sign up to set email alerts
|

Corticotropin-Releasing Factor Acting at the Locus Coeruleus Disrupts Thalamic and Cortical Sensory-Evoked Responses

Abstract: Stress and stress-related psychiatric disorders, including post-traumatic stress disorder, are associated with disruptions in sensory information processing. The neuropeptide, corticotropin-releasing factor (CRF), coordinates the physiological and behavioral responses to stress, in part, by activating the locus coeruleus-norepinephrine (LC-NE) projection system. Although the LC-NE system is an important modulator of sensory information processing, to date, the consequences of CRF activation of this system on s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 49 publications
0
32
1
Order By: Relevance
“…The release of NE is related to arousal states and this in turn has profound effects on cognitive, executive and behavioral processes (Lapiz and Morilak, 2006; Arnsten, 2007). Considering that NE is a key regulator of FC function, either too little or too much adrenergic neurotransmission results in suboptimal neuronal responses to exteroceptive or interoceptive stimuli (Berridge and Waterhouse, 2003; Devilbiss et al, 2012). High levels of noradrenergic transmission are implicated in behavioral, cognitive, emotional and physiological manifestations characteristic of depression and anxiety (Miller et al, 1996; Sands et al, 2000; Cottingham and Wang, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The release of NE is related to arousal states and this in turn has profound effects on cognitive, executive and behavioral processes (Lapiz and Morilak, 2006; Arnsten, 2007). Considering that NE is a key regulator of FC function, either too little or too much adrenergic neurotransmission results in suboptimal neuronal responses to exteroceptive or interoceptive stimuli (Berridge and Waterhouse, 2003; Devilbiss et al, 2012). High levels of noradrenergic transmission are implicated in behavioral, cognitive, emotional and physiological manifestations characteristic of depression and anxiety (Miller et al, 1996; Sands et al, 2000; Cottingham and Wang, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…persistent CRF-induced elevation of tonic LC output. More recently however, Devilbiss et al (2012) showed that intra-LC administration of CRF (300 ng) suppressed sensory evoked responses among ventral posteromedial (VPM) thalamic neurons 0–30 min post-CRF. These results are consistent with those found in the current study, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Dynorphin and κ opioid receptors are coexpressed within the LC on noradrenergic (NA) neurons [67,[82][83][84][85] . Previous reports have shown that both stress and CRF engage in LC NA cell firing [86,87] . Ai-Hasani et al (2013) first reported that κ opioid receptors within the LC NA nuclei modulate the reinstatement of cocaine place preference through a noradrenergic mechanism [88] .…”
Section: Brain Regions Involved In κ Opioid Receptor-mediated Anxietymentioning
confidence: 97%